2011
DOI: 10.1097/aci.0b013e3283466fcb
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of patient compliance in allergic rhinoconjunctivitis

Abstract: The variation in the methodologies used and the durations of treatments assessed in current compliance research in the field of allergic rhinoconjunctivitis decreases the comparability of results. Therefore, a clear definition of compliance measured in clinical trials with allergic rhinoconjunctivitis sufferers is needed. Moreover, a gold standard for measuring and reporting compliance should be determined to enable better interstudy comparability of the rates and determinants of compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 44 publications
2
22
0
2
Order By: Relevance
“…data are in agreement with several previously published studies of patients with PAR, which have reported the rates of around 70-80%[10,15,[17][18][19][20][21][22]. Another study has reported a higher compliance of approximately 97%[20].However, in that study, the patients counted the pills themselves and reported via a Variations caused by the method of compliance measurement were apparent in our study.…”
supporting
confidence: 94%
See 3 more Smart Citations
“…data are in agreement with several previously published studies of patients with PAR, which have reported the rates of around 70-80%[10,15,[17][18][19][20][21][22]. Another study has reported a higher compliance of approximately 97%[20].However, in that study, the patients counted the pills themselves and reported via a Variations caused by the method of compliance measurement were apparent in our study.…”
supporting
confidence: 94%
“…The available data on the patient adherence to allergen-specific immunotherapy are often conflicting [11,12]. In particular, in allergic rhinitis, compliance rates for sublingual administration range between 70% and 97% [10,[13][14][15][16][17][18][19][20][21][22]. This wide variation might be explained by differences in the characteristics and methodology of the studies, such as the population profiles and the definition of compliance [23].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…It is known that lack of efficacy, side effects, treatment duration, and costs are associated with a lower compliance to allergic rhinitis treatment. 18 In a recent Spanish survey, just 15% of allergic rhinitis patients sensitized to dust mites reported an improvement after pharmacological treatment. 19 Another possibility would be that patients with perennial allergic rhinitis do not take adequate treatment due to an effective allergen avoidance.…”
Section: Main Findingsmentioning
confidence: 99%